2003
DOI: 10.3171/jns.2003.99.1.0031
|View full text |Cite
|
Sign up to set email alerts
|

Deep and brainstem cavernomas: a consecutive 8-year series

Abstract: Over the long term, outcomes were worse following conservative treatment or shunt insertion surgery than after microsurgery of symptomatic cavernomas. Incidental cavernomas carried a low risk of neurological deterioration. Surgery should follow generally accepted indications, but only with the confidence that total removal can be safely achieved. Surgery that is performed within 10 to 30 days following ictus may be preferable to delayed surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(103 citation statements)
references
References 20 publications
2
94
0
7
Order By: Relevance
“…10,11,14,19,22,30,34,37,38,42,47,51 Among these studies, Tarnaris et al 47 reported fairly poor outcomes, with 53.3% of patients exhibiting worsening conditions, and cited a neurological deterioration of 10% per patient year. An extremely malignant prognosis was reported with a mortality rate of 20%.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…10,11,14,19,22,30,34,37,38,42,47,51 Among these studies, Tarnaris et al 47 reported fairly poor outcomes, with 53.3% of patients exhibiting worsening conditions, and cited a neurological deterioration of 10% per patient year. An extremely malignant prognosis was reported with a mortality rate of 20%.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…These results compare well with the results of previous series (Table 2). 3,5,8,[15][16][17]21,24,26,31,33,36,38,41 Differences in tumor location, dimension, histology, surgical technique, and grades of resection, along with the absence of a specific subgroup analysis in terms of different surgical approaches, make any comparison difficult. In addition, in our series the small sample size of each group of patients, where different grades of resection could be achieved, prevents further analysis and making definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Small hypointense lesion on T 2 * -weighted images also indicates cavernous malformation or capillary telangiectasia. 5,17,24) These vascular malformations should be ruled out in the assessment of microbleeds.…”
Section: Discussionmentioning
confidence: 99%